New services of the EMBL Data Library. - Fuchs, R (1990)
The existing services of the EMBL Data Library for external users have been improved and extended in several ways. The EMBL File Server has been reorganised, and many new databases and other information relevant to biologists are now accessible via global computer networks. A broad range of software for molecular biology is freely available for different popular computer systems, including the EMBL enhancements to the Wisconsin (GCG) Package. The new Mail-Quicksearch and Mail-FastA services give access to the latest sequence data for database searches by ordinary electronic mail.